Process Intensification of Hydrodealkylation (HDA) for Benzene Production through Heat Integration and Gas Recycle Optimization - Salsabilla Dani; Addila Arrofa’hiya Tri Atqiyani; Aline Arunnisa Isna; Yurieka Berliana; Varel Rahmad Maulana (Journal of Chemical Engineering Research Progress, 2025)
In the hydrodealkylation (HDA) process for benzene production, optimization was achieved through the integration of cryogenic distillation and hydrogen recycling techniques. Using Aspen HYSYS, the process was modeled and analyzed to improve energy efficiency by reusing heat from the waste heat boiler (WHB-01) and the partial condenser (PC-01). The energy recovered from these units was used to preheat both fresh and recycled toluene feeds, significantly reducing the consumption of fresh feed and operational costs. By implementing a hydrogen recycle loop, the process decreased the demand for fresh hydrogen, reducing hydrogen and toluene feed consumption from 125 kmol/h and 196 kmol/h to 111 kmol/h for both. This modification resulted in a conversion rate increase from 70% to 88.9% and achieved energy savings of 84%. The integration of cryogenic separation for methane valorization further enhanced the economic feasibility of the process, turning waste methane into a valuable product. These modifications demonstrated a significant improvement in energy efficiency and sustainability, making the modified HDA process more economically viable for large-scale benzene production. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).